2013
DOI: 10.1158/1535-7163.mct-12-1029
|View full text |Cite
|
Sign up to set email alerts
|

Src Mediates Cigarette Smoke–Induced Resistance to Tyrosine Kinase Inhibitors in NSCLC Cells

Abstract: The EGF Receptor (EGFR) is a proto-oncogene commonly dysregulated in several cancers including non-small cell lung cancer (NSCLC) and, thus, is targeted for treatment using tyrosine kinase inhibitors (TKIs) such as Erlotinib. However, despite the efficacy observed in NSCLC patients harboring oncogenic variants of the EGFR, general ineffectiveness of TKIs in NSCLC patients who are current and former smokers necessitates identification of novel mechanisms to overcome this phenomenon. Previously, we showed that N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 50 publications
0
39
0
Order By: Relevance
“…31 Moreover, other research demonstrated that TKI resistance in exon 21 L858R mutant NSCLC cells after exposure to cigarette smokeeinduced oxidative stress was due to structural alteration of EGFR upon binding of active c-Src to the receptor. 32 Interestingly, this could be eliminated with Src inhibition in vitro, which offered a new rationale for using Src inhibitors to treat TKIresistant NSCLC patients with exon 21 L858R mutation in smokers. 32 It also explained the result from subgroup analysis that nonsmokers received a significant PFS benefit only in the active EGFR-mutant cohort with a larger proportion of exon 21 L858R, instead of the active and nonclassical EGFR-mutant cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Moreover, other research demonstrated that TKI resistance in exon 21 L858R mutant NSCLC cells after exposure to cigarette smokeeinduced oxidative stress was due to structural alteration of EGFR upon binding of active c-Src to the receptor. 32 Interestingly, this could be eliminated with Src inhibition in vitro, which offered a new rationale for using Src inhibitors to treat TKIresistant NSCLC patients with exon 21 L858R mutation in smokers. 32 It also explained the result from subgroup analysis that nonsmokers received a significant PFS benefit only in the active EGFR-mutant cohort with a larger proportion of exon 21 L858R, instead of the active and nonclassical EGFR-mutant cohort.…”
Section: Discussionmentioning
confidence: 99%
“…32 Interestingly, this could be eliminated with Src inhibition in vitro, which offered a new rationale for using Src inhibitors to treat TKIresistant NSCLC patients with exon 21 L858R mutation in smokers. 32 It also explained the result from subgroup analysis that nonsmokers received a significant PFS benefit only in the active EGFR-mutant cohort with a larger proportion of exon 21 L858R, instead of the active and nonclassical EGFR-mutant cohort.…”
Section: Discussionmentioning
confidence: 99%
“…One report suggested that activation of the nicotinic acetylcholine receptor by cigarette smoking induced EGFR-TKI resistance [14]. Another report suggested that smoking induced EGFR posttranslational changes [15] and that the Src oncogene may confer resistance to treatment [16]. Moreover, it was reported that many chemicals contained in cigarette smoke have a high mutagenic activity [17].…”
Section: Discussionmentioning
confidence: 99%
“…Another report proposed that the SRC oncogene may confer resistance to treatment [20]. Additionally, it has been reported that many chemicals contained in cigarette smoke have high mutagenic activity [21]. According to these findings, the rate of genetic alterations is considerably higher in smokers with NSCLC harboring activating EGFR mutations than in nonsmokers with NSCLC harboring EGFR activating mutations [22, 23].…”
Section: Discussionmentioning
confidence: 99%